2020
DOI: 10.1038/s41467-020-18401-z
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement and symmetry of the fungal E3BP-containing core of the pyruvate dehydrogenase complex

Abstract: The pyruvate dehydrogenase complex (PDC) is a multienzyme complex central to aerobic respiration, connecting glycolysis to mitochondrial oxidation of pyruvate. Similar to the E3-binding protein (E3BP) of mammalian PDC, PX selectively recruits E3 to the fungal PDC, but its divergent sequence suggests a distinct structural mechanism. Here, we report reconstructions of PDC from the filamentous fungus Neurospora crassa by cryo-electron microscopy, where we find protein X (PX) interior to the PDC core as opposed to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 49 publications
7
63
0
Order By: Relevance
“…However, we were not able to unambiguously assign the individual E1p and/or E3 components into a complete model due to the conformational flexibility and compositional heterogeneity of the outer shell (Supplementary Fig. 4a ), which is not geometrically precise and does not exactly follow the symmetry of the E2p core 6 , 8 , 9 , 28 , 29 , 40 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, we were not able to unambiguously assign the individual E1p and/or E3 components into a complete model due to the conformational flexibility and compositional heterogeneity of the outer shell (Supplementary Fig. 4a ), which is not geometrically precise and does not exactly follow the symmetry of the E2p core 6 , 8 , 9 , 28 , 29 , 40 .…”
Section: Resultsmentioning
confidence: 92%
“…It is structurally and functionally related to the other oxoacid dehydrogenase complexes: α-ketoglutarate dehydrogenase complex (E1o, E2o, and E3) and branched-chain α-ketoacid dehydrogenase complex (E1b, E2b, and E3), which all have individual E1 and E2 subunits but share a common E3 component 6 . Mitochondrial PDHc contains an E3-binding protein (protein X), and its activity is additionally regulated by E1 kinases and phosphatases 7 9 . In the first reaction step catalyzed by E1p, pyruvate is decarboxylated using thiamine pyrophosphate (TPP, also often referred to as TDP or ThDP for thiamine/vitamin B1 diphosphate) as a cofactor and the resulting hydroxyethyl-TPP then reacts with lipoamide (oxidized lipoic acid attached to a lysine residue of E2p 10 ) to produce S-acetyldihydrolipoamide and recover the TPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that exogenous glucose uptake into cells is mediated by glucose transporters (GLUTs), and glucose metabolism is catalyzed by several key enzymes, including HKs and PDHX ( Gershon et al, 2013 ; Adeva-Andany et al, 2016 ; Forsberg et al, 2020 ). To determine whether SGIV infection activated glycolysis, the transcription levels of HK2, PDHX, GLUT1, and GLUT2 were firstly examined in vivo by qPCR during SGIV infection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, hexokinases (HKs), which convert glucose to glucose 6-phosphate, is the first and rate-limiting enzyme in glycolytic pathway and the HK2 isoform is a key mediator of aerobic glycolysis ( Wolf et al, 2011 ; Gershon et al, 2013 ). Pyruvate dehydrogenase complex (PDHX), which provide acetyl-CoA for the TCA cycle, is a multienzyme complex central to aerobic respiration, connecting glycolysis to mitochondrial oxidation of pyruvate ( Forsberg et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%